2013
DOI: 10.2224/sbp.2013.41.3.357
|View full text |Cite
|
Sign up to set email alerts
|

How Followers' Unethical Behavior is Triggered by Leader-member Exchange: the Mediating Effect of Job Satisfaction

Abstract: exchange (LMX) has been shown to be related to positive outcomes. However, little attention has been paid to the relationship between LMX and negative organizational behaviors such as unethical behavior. In this study we investigated 249 Chinese managers in 4 different finance companies in China, and found that there is a mediating effect of job satisfaction on the negative relationship between LMX and unethical behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…The increment in the percentage of variance being explained by LMX and job satisfaction to 42.8% further reaffirmed that when employees with high satisfaction were always thankful to the organization and were likely to produce positive behaviors such as OCB as a gesture of "pay back" the organization. This finding was also congruent with that in non-Western context based on the findings by Kasemsap (2013) in textile factories operating in Thailand, Songbo et al (2013) and Cheung and Wu (2013) in Chinese firms which these researches found the positive mediating effect of job satisfaction in improving employees work outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…The increment in the percentage of variance being explained by LMX and job satisfaction to 42.8% further reaffirmed that when employees with high satisfaction were always thankful to the organization and were likely to produce positive behaviors such as OCB as a gesture of "pay back" the organization. This finding was also congruent with that in non-Western context based on the findings by Kasemsap (2013) in textile factories operating in Thailand, Songbo et al (2013) and Cheung and Wu (2013) in Chinese firms which these researches found the positive mediating effect of job satisfaction in improving employees work outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Though these companies and participants represented various backgrounds in China, future studies are still needed to examine whether or not our findings can be replicated or extended outside China or in other organizational contexts. Third, more attention should be paid to the relationship between LMX and negative organizational behaviors (Liu, Lin, & Hu, 2013). Future researchers could explore the mediating effect of identification on the relationship between LMX and negative attitude and behavior, such as workplace deviant behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the leader-member exchange (LMX) relationship between leaders and followers (Dienesch and Liden, 1986;Graen and Uhl-Bien, 1995;Settoon et al, 1996) appears to play a prominent role in preventing employee unethical behavior. Under the assumption that followers aim to positively reciprocate high-quality LMX relationships, initial studies have demonstrated that LMX is negatively related to self-serving behaviors such as deviance, counterproductive work behaviors, and withdrawal (Gerstner and Day, 1997;El Akremi et al, 2010;Liu et al, 2013;Jawahar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In these recent studies, followers are assumed to use pro-leader unethical behaviors to positively reciprocate the benefits they receive from their leaders in high-quality LMX relationships. As such, this positive reciprocity mechanism is used in research to explain both why high-quality LMX relationships demotivate (El Akremi et al, 2010;Liu et al, 2013;Jawahar et al, 2018) and motivate (Umphress et al, 2010;Bryant and Merritt, 2019) unethical behaviors. That is, the negative effects of LMX on self-serving unethical behavior and its positive effects on other-serving unethical behavior are assumed to be driven by the same motivational mechanism of positive reciprocity.…”
Section: Introductionmentioning
confidence: 99%